Pharmacology Content: Learning in a Playful Way - Zepponi, Karla Meira Castro; Braccialli, Luzmarina Aparecida Doretto; Pinheiro, Osni Lazaro [UNESP] (Ludomedia Unipessoal Lda, 2021)
Introduction In professional training, the use of an educational game associated with situations of pharmacology practice provided the student with a concrete and playful form of learning. Objective: To analyze the use of an educational game in a playful way with the application of basic pharmacology concepts. Method: Qualitative study, with an observational and descriptive approach. Data collection was carried out with judges with experience in teaching and in pharmacology. The judges validated the game by means of a questionnaire that contained an open field which made their considerations and suggestions for improvements. The nuclei of meaning and a content analysis in the thematic modality were listed. Results: The themes were: Facilities to learn basic pharmacology concepts through a game and Difficulties encountered to learn basic pharmacology concepts, both were worked to seek improvement in the game and its contents. Final considerations: The games were validated by the judges who pointed out relevant suggestions to improve the didactic material, the content, the rules of the game and to enable a compatible learning to the technical teaching of pharmacy.
Farmacologia: O aprendizado de forma lúdica
Keywords: Game; Learning; Pharmacology; Teaching; Teaching Materials